Description of Knowledge About Reproductive Health in Youth at Muhammadiyah University Jakarta 2021 - Andi Bunga; Ranti Salsabila; Rehan Aula; Shania Maharani (Fakultas Kesehatan Masyarakat Universitas Muhammadiyah Jakarta, 2021)
Reproductive health is a state of complete physical, mental and social well-being. The main problem of Indonesian youth is ignorance of the actions that must be taken, especially reproductive health problems. This is indicated by the low knowledge of adolescents about reproductive health. This study aims to determine the description of reproductive health knowledge in adolescents, Muhammadiyah University, Jakarta. This type of research is descriptive using a qualitative approach. The subjects in the study were 4 adolescent informants. Data collection techniques with in-depth interviews and observation. Adolescent knowledge about reproductive health is obtained through the internet and courses. In maintaining the health of their reproductive organs, teenagers live a healthy life and avoid risky sexual behavior. As a result of risky sexual behavior that can be exposed to sexually transmitted diseases such as HIV / AIDS and others. In controlling their reproductive health, adolescents have never been examined by health services. The view of teenagers regarding deviant sexual behavior is that it is illegal which if done is a big sin and can interfere with brain health.